2019
DOI: 10.1103/physrevb.100.224104
|View full text |Cite
|
Sign up to set email alerts
|

Structure of liquid ammonia at high pressures and temperatures

Abstract: The structure of liquid ammonia (NH3) is investigated from 1 to 6.3 GPa and up to 800 K by means of synchrotron x-ray diffraction (XRD) and ab initio molecular dynamics (AIMD) simulations. The XRD data are used to extract the molecular structure factor S mol (Q), pair distribution function (PDF) g mol (r), and the density of NH3. There is an excellent agreement between present S mol (Q) and g mol (r) at our lowest density and those reported in reference neutron experiments. Our densities agree better with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In particular, not only the spatial extent of the first solvation shell of the ammonia molecules is expanded, but also the population of first-neighboring species increases upon the field action, as reported in the inset of Figure 3 . In fact, starting from a coordination number of 12.0 in the zero-field case ( vis-à-vis an experimental value of 12.7 49 ), it reaches a maximum value of ∼15.7 for a field strength of 0.40 V/Å, which decreases to ∼5.9 above this field threshold. On the other hand, it has to be noticed that the first local minimum of the NN RDF at strong field regimes exhibits a height larger than 1 and that the integral up to the second (far deeper) minimum leads to a coordination number equal to ∼11.1, as displayed in Figure S8 of the SI.…”
mentioning
confidence: 88%
“…In particular, not only the spatial extent of the first solvation shell of the ammonia molecules is expanded, but also the population of first-neighboring species increases upon the field action, as reported in the inset of Figure 3 . In fact, starting from a coordination number of 12.0 in the zero-field case ( vis-à-vis an experimental value of 12.7 49 ), it reaches a maximum value of ∼15.7 for a field strength of 0.40 V/Å, which decreases to ∼5.9 above this field threshold. On the other hand, it has to be noticed that the first local minimum of the NN RDF at strong field regimes exhibits a height larger than 1 and that the integral up to the second (far deeper) minimum leads to a coordination number equal to ∼11.1, as displayed in Figure S8 of the SI.…”
mentioning
confidence: 88%
“…27 Furthermore, Calliol et al found that the radial distribution function curves by the hypernetted chain (HNC) and the reference hypernetted chain are found to be in good accordance with experimental data 25 for the nitrogen-nitrogen distribution function at 4 ∘ C. 28 Besides, Queyroux et al, in their paper investigating at high pressures and temperatures the structure of liquid ammonia by synchrotron X-ray diffraction, reported that above 1 GPa and up to 6.3 GPa at 800 K ammonia structures revealed a close packing form. 29 Characterization of ammonia structure in the liquid phase by radial distribution function done by Gao et al exhibits a formation of an average of three hydrogen bonds per ammonia molecule, and the liquid is made up of winding chains of hydrogen-bonded monomers. Roughly linear hydrogen bonds predominate in the liquid phase.…”
mentioning
confidence: 99%
“…Despite its importance, experimental studies of the high pressure behavior of ammonia remain very scarce and limited to a narrow thermodynamic range. Measurements in diamond anvil cells have characterized the equation of state and phase diagram up to 200 GPa at 300 K, but reached at most ∼40 GPa at higher temperatures (∼3000 K) [29][30][31][32][33][34][35][36]. Few studies have been carried out employing dynamic compression methods, mainly at gasgun facilities, providing shock compression data up to 70 GPa [37][38][39][40][41][42].…”
mentioning
confidence: 99%